2006
DOI: 10.1111/j.1537-2995.2006.00803.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage of buffy coat–derived platelets in additive solutions: in vitro effects of storage at 4°C

Abstract: PLTs stored at 4 degrees C without agitation maintain metabolic and cellular characteristics to a great extent during 21 days of storage. These studies confirm the view that PLTs lose their discoid shape and that this loss with storage at 4 degrees C is associated with reductions in metabolic rate and in their release of alpha-granule content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
79
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(97 citation statements)
references
References 25 publications
17
79
0
1
Order By: Relevance
“…Platelet concentrate (PC) is recently stored for a maximum of 5-7 days due to the risk of bacterial growth [2]. Many factors influence the quality of platelets during storage including the preparation method [3], the material of the storage bag [4], the bag ability to gas exchange [3], and the storage temperature [5,3]. During storage, platelets undergo numerous changes due to lactate accumulation and a decrease in pH [6].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet concentrate (PC) is recently stored for a maximum of 5-7 days due to the risk of bacterial growth [2]. Many factors influence the quality of platelets during storage including the preparation method [3], the material of the storage bag [4], the bag ability to gas exchange [3], and the storage temperature [5,3]. During storage, platelets undergo numerous changes due to lactate accumulation and a decrease in pH [6].…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have reported the presence of increased platelet activation markers such as exposure of surface P-selectin [11,37,38] following refrigeration, indicating that platelet refrigeration can induce some α-granule release. However, other investigators have reported the opposite, that refrigeration (< 21 days) retards the release of α-granule contents such as β-thromboglobulin [12,39,40]. Refrigerated platelets spontaneously form aggregates [41,42], respond better to agonists than room temperature platelets [11,[43][44][45][46][47][48][49][50][51], and adhere better to von Willebrand factor (vWf) under shear stress [52,53].…”
Section: Room Temperature Versus Refrigerated Storagementioning
confidence: 99%
“…It measures the ability of platelets to recover from a hypotonic challenge with the notion that only 'metabolically fit' platelets recover. Since refrigerated platelets perform poorly in this assay [12], investigators have proposed that refrigeration impairs platelet adenosine triphosphate (ATP) production [58,59]. It has also been reported that exposure of platelets to low temperatures can induce mitochondrial damage [60,61] providing a mechanism for altered ATP metabolism.…”
Section: Room Temperature Versus Refrigerated Storagementioning
confidence: 99%
See 2 more Smart Citations